Prevalence of chronic suppurative otitis media in school children of Kathmandu district - Adhikari, P; Sinha, BK; Pokharel, NR; Kharel, B; Aryal, R; Ma, J (Journal of Institute of Medicine Nepal, 2008)
Background: Chronic suppurative otitis media is a major health problem throughout the world in developing countries including Nepal. This study was carried out to find the prevalence of chronic suppurative otitis media (CSOM) among school going children of Kathmandu district. Methods: This is a prospective cross sectional study among 1070 school children aged between 5 - 12 years. Students were randomly selected from four different schools of Kathmandu district. All these students were interviewed and examined otoscopically from November 2006 to January 2007. Data were analyzed statistically. Results: Results showed that 5.4% of the children had CSOM. Unilateral disease was seen in 79.3% and 96.5% had a tubotympanic disease. Around 24.1% had active disease, 65.4% used unhygienic and risky materials to clean their ears. There were 10.3% students having CSOM who did not receive any treatment. More than half were treated by paramedics. Conclusion: The prevalence of CSOM among school children in Kathmandu district is lower as compared to rural areas of Nepal. This might be due to the improvement of health care facilities or due to increase in the use of antimicrobials in Kathmandu. Awareness for school children as well as parents through health education is in need to reduce the prevalence of CSOM. Key words: Chronic suppurative otitis media (CSOM), tubotympanic disease, health education. The full text of this paper is available at Journal of Institute of Medicine website